Elements of fatherhood involved in the gestational period: a scoping review - Willyane de Andrade Alvarenga; Maria da Conceição Silva Castro Sousa; Joice Kelly Lima de Sales; Rhyquelle Rhibna Neris; Francine DeMontigny; Lucila Castanheira Nascimento (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To identify in the literature and summarize the elements and characteristics of fatherhood involved during pregnancy. Method: Scoping review that used PRISMA-ScR guide to report this review. Searches were carried out in PubMed, CINAHL, PsycInfo, LILACS and Scopus. Google search engines and public health agency websites assisted in searches of gray literature and Rayyan in screening studies. Results: A total of 406 articles were identified, of which 16 made up the final sample. Five elements make up an involved fatherhood: feeling like a father, being a provider and protector, being a partner and participant in pregnancy, participating in prenatal appointments and feeling prepared to take care of a baby. Conclusion: Fathers want to be involved in prenatal care, but feel excluded from this process. Public policies that encourage paternal involvement and healthcare professional training to better welcome and promote paternal involvement are of paramount importance.